Promotion of Early Gut Colonization by Probiotic Intervention on Microbiota Diversity in Pregnant Sows - Veljović, Katarina; Dinić, Miroslav; Lukić, Jovanka; Mihajlović, Sanja; Tolinački, Maja; Živković, Milica; Begović, Jelena; Mrvaljević, Igor; Golić, Nataša; Terzić-Vidojević, Amarela (Frontiers in Microbiology, 2017)
The aim of this work was to design a novel mixed probiotic culture for piglets and to evaluate its beneficial effect on the piglets’ gut health. The possible mechanisms of probiotic activity, such as adhesion, competitive pathogen exclusion and influence on gut microbiota diversity were determined. Mixed probiotic starter culture is composed of three thermophilic lactic acid bacteria (LAB) strains: Lactobacillus helveticus BGRA43, Lactobacillus fermentum BGHI14 and Streptococcus thermophilus BGVLJ1-44. The strains BGVLJ1-44 and BGRA43 showed good technological properties (fast milk curdling, strong proteolytic activity). In addition, the strain BGVLJ1-44 produces exopolysaccharide (EPS), BGHI14 is heterofermentative LAB strain with significant immunomodulatory effect, while the strain BGRA43 showed strong antimicrobial activity against different pathogens and exhibited significantly higher level of adhesion to Caco-2 cells comparing to other two strains. Both lactobacilli strains BGRA43 and BGHI14 (p<0.05), as well as probiotic combination (p<0.01) significantly reduced the adhesion of Escherichia coli ATCC25922 to Caco-2 cells, while the strains BGVLJ1-44 (p<0.01) and BGRA43 (p<0.05) significantly reduced adhesion of Salmonella 654/7E (veterinary isolate). The results of farm trial revealed that treatment of sows with new fermented dairy probiotic influenced the piglets’ gut colonization with beneficial bacteria and reduced the number of enterobacteriaceae in litters from some treated sows (no significant due to high variability among animals). Finally, this is the first study reporting that the treatment of sows with probiotic combination resulted in the improved microbiota diversity in neonatal piglets.